Obstetric complications in women with IVF conceived pregnancies and polycystic ovarian syndrome - Sunita R Tandulwadkar; Pooja A Lodha; Nirzari T Mangeshikar (Wolters Kluwer Medknow Publications, 2014)
Polycystic ovarian syndrome (PCOS) is often accompanied by infertility that necessitates ovulation induction using clomiphene citrate, gonadotropins or even in vitro fertilization (IVF). These treatment methods are known to increase the incidence of multiple pregnancies as well as some negative consequences, including a rise in the risk for gestational diabetes mellitus, pre-eclampsia, etc., Furthermore, pregnancies established after IVF carry an increased risk for maternal complications. However, the increased risk of developing adverse obstetric complications has been suggested to occur independently of obesity as well as in populations without assisted reproductive techniques. Many studies have been performed to study the effect of PCOS on pregnancy and the effect of pregnancy on PCOS. The hormonal milieu that is exaggerated in PCOS women is quite well understood at the biochemical and genetic levels. The maternal and neonatal outcomes of PCOS women who have undergone in vitro fertilization-embryo transfer (IVF-ET) have not been widely studied till date. This review aims to evaluate the current evidence regarding adverse obstetric outcomes of PCOS women undergoing IVF-ET. The rationale of this review is to study whether the adverse obstetric outcomes are increased in PCOS women in general, or particularly in those PCOS women who are undergoing IVF-ET. It is also important to analyze via a literature review whether the increased adverse outcomes are due to infertility in general or PCOS per se. An attempt has been made to give evidence regarding preventive strategies for obstetric complications in PCOS women who have undergone IVF-ET.